2010
DOI: 10.1002/bip.21376
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the proteinase inhibitor LEKTI domain 6 by the fragment condensation method and regioselective disulfide bond formation

Abstract: Proteinase inhibitors are of high pharmaceutical interest and are drug candidates for a variety of indications. Specific kallikrein inhibitors are important for their antitumor activity and their potential application to the treatment of skin diseases. In this study we describe the synthesis of domain 6 of the kallikrein inhibitor Lympho-Epithilial Kazal-Type Inhibitor (LEKTI) by the fragment condensation method and site-directed cystine bridge formation. To obtain the linear LEKTI precursor, the condensation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Phage-display peptide screening has been successfully used for the discovery of KLK2-inhibiting peptides as promising imaging probes for use in prostate cancer 192,193 . De novo solidphase synthesis efforts for the development of peptidebased KLK inhibitors are exemplified by: the synthesis of LEKTI-peptide domain 6 as a potent KLK5 and KLK7 inhibitor; the design of azapeptide-based inhibitors of KLK3; and the development of KLK1 inhibitors (for example, compound 1 in TABLE 2) from modified N-sulfonyltripeptides [194][195][196] .…”
Section: Peptide-based Klk Inhibitorsmentioning
confidence: 99%
“…Phage-display peptide screening has been successfully used for the discovery of KLK2-inhibiting peptides as promising imaging probes for use in prostate cancer 192,193 . De novo solidphase synthesis efforts for the development of peptidebased KLK inhibitors are exemplified by: the synthesis of LEKTI-peptide domain 6 as a potent KLK5 and KLK7 inhibitor; the design of azapeptide-based inhibitors of KLK3; and the development of KLK1 inhibitors (for example, compound 1 in TABLE 2) from modified N-sulfonyltripeptides [194][195][196] .…”
Section: Peptide-based Klk Inhibitorsmentioning
confidence: 99%
“…N or S ? O shift of the Acm group from Cys to a side chain of Asn, Gln, Lys, Ser, Thr or Tyr may occur easily (Vasileiou et al 2010). To avoid formation of this side product after completion of the reaction and workup procedure, the residual aqueous solution was concentrated by lyophilization to only ca 10% of original volume.…”
Section: Resultsmentioning
confidence: 99%
“…19,29,31,[50][51][52][53][54] In collaboration with Dr. Schechter, we studied the effects of LEKTI domains 6-9 and 9-12 on the in vitro activity and binding of human recombinant KLK5 and KLK7. 50 We demonstrated for the first time that LEKTI domains 6-9 strongly inhibited the activity of both KLK5 and KLK7 with a Ki of 5nM and 11nM respectively.…”
Section: Recombinant Lekti Inhibit a Broad Spectrum Of Proteinasesmentioning
confidence: 99%
“…We have observed that the product formation over the 60 min assay period in the absence and presence of inhibitor was linear with respect to time. 19,31,49,54 The linear shapes of these inhibition curves indicate that rLEKTI is not a time-dependent inhibitor, suggesting that LEKTI binds rapidly to these proteinases and inactivates them. To classify the type of inhibition, the kinetic constants (Km and Vmax) of plasmin, trypsin, subtilisin A, cathepsin G, HNE, KLK5, KLK6, KLK13 and KLK14 were determined for their respective chromogenic or flurogenic peptides in the presence of increasing concentrations of different rLEKTI species.…”
Section: Recombinant Lekti Inhibit a Broad Spectrum Of Proteinasesmentioning
confidence: 99%